PREDICTION OF THE EFFICIENCY OF SIEVE TRAY USING AIRWATER SYSTEM (Journal of Engineering, 2006)
This investigation deals with the effect of weir height, liquid and gas flow rate on tray efficiency.The tests were carried out on a single pass cross flow tray of air-water system of 0.3 m diameter for clearliquid height over sieve tray with weir height 3, 4 and 5 cm.Point efficiency values were found to be in the same range for different weir height, but itimproves slightly with weir height. And the average values of point efficiency were 83 % for 3 cm weirheight, 85 % for 4 cm weir height and 89 % for 5 cm weir height. While, point efficiency of 90 % was obtained for 5 cm weir height and liquid flow rate ranging between 5.8 to 7.32 m3/s. In the range of clear liquid height over hole diameter ( hL/dH) between 2 to 10, increasing the Reynolds number ranging between 2.0*105 to 1.6*106 for gas phase increases point efficiency. Prediction of Murphree (Tray) efficiency using Lopez and Castells (1999) equation shows that the ratio of EMV/Ep is equal to 1, due to low value of calculated Peclet number (degree of liquid mixing), which ranged between 0.07 to 1.5.